Pembelajaran Kolaboratif Melalui Strategi Writing From A Prompt dan Writing in Performance Tasks Dalam Upaya Meningkatkan Kemampuan Menulis Matematis Siswa SMP - Ratu Mauladaniyati (Universitas Mathla'ul Anwar Banten, 2015)
Mathematics is very important lesson to learn by students. But, in the reality most of the students are get low result in mathematics. One of the problem is the weakness of the skill to communicate the ideas systematically. It caused by the mathematical writing skill students and it is part of communication aspect that has not developed yet optimally. One of teaching alternative it can be used to increase the mathematical writing skill students is teaching collaborative through Writing from A Prompt (WfAP) strategy and Writing in Performance Tasks (WiPT) strategy. The purpose of this research is to know the influence of collaborative teaching through WfAP strategy and through WiPT strategy to the increase of mathematical writing skill at junior high school students. This method use experiment research and the data analysis of this research use test one way ANOVA and test Scheffe. Based on the data analysis it can be conclude that there are the differences between the mathematical writing skill students who get collaborative teaching through WfAPstrategy, collaborative teaching through WiPTstrategy, and convensional teaching. The mathematical writing skill students who get collaborative teaching through WfAP strategy and collaborative teaching through WiPTstrategy better than convensional teaching.